Distinct heat response molecular mechanisms emerge in cassava vasculature compared to leaf mesophyll tissue under high temperature stress - Wang, Shujuan; Zhou, Xincheng; Pan, Kun; Zhang, Huaifang; Shen, Xu; Luo, Jia; Li, Yuanchao; Chen, Yinhua; Wang, Wenquan (Frontiers in Plant Science, 2023)
With growing concerns over global warming, cultivating heat-tolerant crops has become paramount to prepare for the anticipated warmer climate. Cassava (Manihot esculenta Crantz), a vital tropical crop, demonstrates exceptional growth and productivity under high-temperature (HT) conditions. Yet, studies elucidating HT resistance mechanisms in cassava, particularly within vascular tissues, are rare. We dissected the leaf mid-vein from leaf, and did the comparative transcriptome profiling between mid-vein and leaf to figure out the cassava vasculature HT resistance molecular mechanism. Anatomical microscopy revealed that cassava leaf veins predominantly consisted of vasculature. A thermal imaging analysis indicated that cassava experienced elevated temperatures, coinciding with a reduction in photosynthesis. Transcriptome sequencing produced clean reads in total of 89.17G.Using Venn enrichment, there were 65 differentially expressed genes (DEGs)DEGs and 93 DEGs had been found highly specifically expressed in leaf and mid-vein.Further investigation disclosed that leaves enhanced pyruvate synthesis as a strategy to withstand high temperatures, while mid-veins fortified themselves by bolstering lignin synthesis by comprehensive GO and KEGG analysis of DEGs. The identified genes in these metabolic pathways were corroborated through quantity PCR (QPCR), with results aligning with the transcriptomic data. To verify the expression localization of DEGs, we used in situ hybridization experiments to identify the expression of MeCCoAMT(caffeoyl-coenzyme A-3-O-methyltransferase) in the lignin synthesis pathway in cassava leaf veins xylem. These findings unravel the disparate thermotolerance mechanisms exhibited by cassava leaves and mid-veins, offering insights that could potentially inform strategies for enhancing thermotolerance in other crops.